128k views
25 votes
HELP ME PLEAASSEEEEEE​

HELP ME PLEAASSEEEEEE​-example-1

1 Answer

2 votes

Answer:

see explanation

Explanation:

(i)

to find h(g(x)) , substitute x = g(x) into h(x) , that is

h(g(x))

= h(2x - 3)

= 4(2x - 3)

= 8x - 12

(ii)

given

h(g(x)) =
(1)/(2) g(x) , then

8x - 12 =
(1)/(2) (2x - 3) ← multiply both sides by 2 to clear the fraction

16x - 24 = 2x - 3 ( subtract 2x from both sides )

14x - 24 = - 3 ( add 24 to both sides )

14x = 21 ( divide both sides by 14 )

x =
(21)/(14) =
(3)/(2) = 1.5

User Bull
by
5.3k points